An analysis of ionospheric response to geomagnetic disturbances over South Africa and Antarctica - Ngwira, Chigomezyo Mudala (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2012)
The ionosphere is of practical importance for satellite-based communication and navigation systems due to its variable refractive nature which affects the propagation of trans-ionospheric radio signals. This thesis reports on the first attempt to investigate the mechanisms responsible for the generation of positive ionospheric storm effects over mid-latitude South Africa. The storm response on 15 May 2005 was associated with equatorward neutral winds and the passage of travelling ionospheric disturbances (TIDs). The two TIDs reported in this thesis propagated with average velocities of âˆ¼438 m/s and âˆ¼515 m/s respectively. The velocity of the first TID (i.e. 438 m/s) is consistent with the velocities calculated in other studies for the same storm event. In a second case study, the positive storm enhancement on both 25 and 27 July 2004 lasted for more than 7 hours, and were classified as long-duration positive ionospheric storm effects. It has been suggested that the long-duration positive storm effects could have been caused by large-scale thermospheric wind circulation and enhanced equatorward neutral winds. These processes were in turn most likely to have been driven by enhanced and sustained energy input in the high-latitude ionosphere due to Joule heating and particle energy injection. This is evident by the prolonged high-level geomagnetic activity on both 25 and 27 July. This thesis also reports on the phase scintillation investigation at the South African Antarctic polar research station during solar minimum conditions. The multi-instrument approach that was used shows that the scintillation events were associated with auroral electron precipitation and that substorms play an essential role in the production of scintillation in the high latitudes. Furthermore, the investigation reveals that external energy injection into the ionosphere is necessary for the development of high-latitude irregularities which produce scintillation. Finally, this thesis highlights inadequate data resources as one of the major shortcomings to be addressed in order to fully understand and distinguish between the various ionospheric storm drivers over the Southern Africa mid-latitude region. The results presented in this thesis on the ionospheric response during geomagnetic storms provide essential information to direct further investigation aimed at developing this emerging field of study in South Africa.
Keywords: Geomagnetism -- South Africa; Geomagnetism -- Antarctica; Ionospheric storms -- South Africa; Ionospheric storms -- Antarctica